2018
DOI: 10.1002/iroh.201801940
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic activity of the bloom‐forming picocyanobacterium Synechococcus sp. on the coexisting microalgae: The role of eutrophication

Abstract: Allelopathic picocyanobacteria have been responsible for harmful incidents with severe ecological impacts in many parts of the world. The allelopathic interactions that have been shown to be implied in the dominance of various species of phytoplankton, forming massive blooms, are influenced by environmental factors such as nutrient concentration. This study aims to determine in what extent the allelopathic activity of the bloom‐forming picocyanobacterium Synechococcus sp. is impacted by water stoichiometry. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Contrary to that, Synechococcus sp. filtrate had no allelopathic effects on Oocystis submarina Lagerheim [23,24]. In our work we have shown that Synechococcus sp.…”
Section: Discussionmentioning
confidence: 47%
See 4 more Smart Citations
“…Contrary to that, Synechococcus sp. filtrate had no allelopathic effects on Oocystis submarina Lagerheim [23,24]. In our work we have shown that Synechococcus sp.…”
Section: Discussionmentioning
confidence: 47%
“…That study pointed to the diatoms of the genera Navicula, Chaetoceros, Amphora, Coscinodiscus, Grammatophora, and Nitzschia as the most allelochemical-sensitive organisms. Moreover,Śliwińska-Wilczewska and Latała [23],Śliwińska-Wilczewska et al [24], and Konarzewska et al [26] demonstrated that the addition of Synechococcus sp. filtrate strongly inhibited the growth of Skeletonema marinoi Sarno and Zingone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations